Low-Cost, Farmer-Friendly Substrates for Seed Germination Testing: Evidence across Major Field Crops - KALYANI KUMARI; KALYANRAO; BANOTH VINESH; ANJANI KU SINGH; PAVITHRA V; SANJAY KUMAR; SUNIL KANNUJIA (Seed Research, 2025)
Seed germination testing is a critical yet often inaccessible component of seed quality assurance,particularly for smallholder farmers who rely heavily on farm-saved or locally sourced seed. Conventional laboratorybased germination tests, though scientifically robust, remain beyond the reach of many farming communities dueto cost, infrastructure, and logistical constraints. The present study evaluated the effectiveness of three substrates—germination paper, newspaper, and jute (gunny) bag—on seed quality parameters of ten economically importantcrops, including major cereals (wheat, paddy, and barley), pulses (green gram, chickpea, pea, lentil, and cowpea),and oilseeds (soybean and mustard). Germination percentage (GERMI%), seedling dry weight (DW), shoot length(SL), root length (RL), and vigour indices (VI-I and VI-II) were recorded and statistically analysed. Results revealedthat germination percentage across all three substrates was statistically at par for most crops, indicating that lowcost alternatives can provide reliable estimates of seed viability. Although germination paper produced superiorseedling growth and vigour, newspaper and gunny bag substrates demonstrated consistent and dependableperformance. These findings highlight the potential of low-cost, locally available substrates to serve as practicaltools for on-farm and community-level seed quality assessment, thereby strengthening decentralized seed systems,supporting extension-led advisory services, and enabling evidence-based seed management decisions underresource-constrained conditions.